2002
DOI: 10.1029/2000jc000583
|View full text |Cite
|
Sign up to set email alerts
|

Tracer studies of pathways and rates of meltwater transport through Arctic summer sea ice

Abstract: At the Surface Heat Budget of the Arctic Ocean (SHEBA) program's field site in the northern Chukchi Sea, snow and ice meltwater flow was found to have a strong impact on the heat and mass balance of sea ice during the summer of 1998. Pathways and rates of meltwater transport were derived from tracer studies (H218O, 7Be, and release of fluorescent dyes), complemented by in situ sea‐ice permeability measurements. It was shown that the balance between meltwater supply at the surface (averaging between 3.5 and 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
410
1
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 268 publications
(454 citation statements)
references
References 39 publications
15
410
1
5
Order By: Relevance
“…Melt Pond Class: Residual objects with means greater than (B) were classified as melt ponds (Figures 2c1-2c2). The image classification is complete at Step 6 for scenes exhibiting melt Stage 1 (pond formation) and melt Stage 2 (pond drainage) [Eicken et al, 2002;Polashenski et al, 2012]. Total computation time, including cloud and open water masking, is 15 min on an Intel i7 eight-core processor machine.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melt Pond Class: Residual objects with means greater than (B) were classified as melt ponds (Figures 2c1-2c2). The image classification is complete at Step 6 for scenes exhibiting melt Stage 1 (pond formation) and melt Stage 2 (pond drainage) [Eicken et al, 2002;Polashenski et al, 2012]. Total computation time, including cloud and open water masking, is 15 min on an Intel i7 eight-core processor machine.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…Especially evident on undeformed first-year ice, the lateral spread of meltwater can cause maximum pond fractions as high as 70% due to the low surface topography of snow drift bed forms [Scharien and Yackel, 2005;Petrich et al, 2012a;Polashenski et al, 2012]. On a broader scale, Webster et al [2014] have shown that snow depth distributions on both ice types in the western Arctic have decreased, and may have two effects on melt pond formation (1) more thinly snow-covered ice and bare ice may expose the ice surface to solar radiation earlier in the season and hasten melt, and (2) less freshwater may be available during early pond formation to form low-salinity ice surface layers [Eicken et al, 2002], which further motivates an analysis of seasonal melt pond evolution on drifting sea ice in more recent years.…”
Section: Introductionmentioning
confidence: 99%
“…На основе дан-ных, полученных с сонара, в работе [10] сделан вывод о том, что образование подлёдных прудов должно быть широкораспространённым явлением в Арк-тике, а в работе [11] показано, что над подлёдными прудами часто находятся поверхностные пруды, что подтверждает механизм образования ложного дна, изображенный на рис. 1 по данным работ [8,12].…”
unclassified
“…Ложное дно достаточно часто наблюдалось в полевых экспериментах SHEBA [12,13]. При этом было отмечено, что начальное образование ложно-го дна обычно занимало пару часов; большие кристаллы льда претерпевали боковой рост от стенок, образуя поверхность ложного дна.…”
unclassified
See 1 more Smart Citation